Wealth, Information Acquisition, and Portfolio Choice - Peress, Joël (Review of Financial Studies, 2004)
I solve (with an approximation) a Grossman-Stiglitz economy under general preferences, thus allowing for wealth effects. Because information generates increasing returns, decreasing absolute risk aversion, in conjunction with the availability of costly information, is sufficient to explain why wealthier households invest a larger fraction of their wealth in risky assets. One no longer needs to resort to decreasing relative risk aversion, an empirically questionable assumption. Furthermore, I show how to distinguish empirically between these two explanations. Finally, I find that the availability of costly information exacerbates wealth inequalities.